Effect of varying nitrogen application frequency on rice growth and production / Siti Aishah Mohamad Sakroji - Mohamad Sakroji, Siti Aishah (Faculty of Plantation and Agrotechnology, 2019)
Rice is a staple food consumed by nearly 7 million people worldwide. The rate of consumption is increase as the number of population increase. Therefore, higher rice production is required to fulfil the demand. Decrease in rice production can be caused by several factors and one of them is nutrient management especially nitro-gen fertilizer. Nitrogen is the basic nutrient needed by rice and helps in maintaining the rice production. The quality and production of rice can be improved if the use of urea fertilizers is administered as efficiently and effectively as possible for fertilization. The study was conducted in UITM Jasin greenhouse Melaka using Randomized Completely Block Design (RCBD) with 3 block, four treatment and two rice varieties, MR219 and MR269. The first treatment (T1) were four times application of urea fertilizer (15th, 35th, 55th and 75th days after sowing).Second treatment (T2) was three times application of urea (20th, 45th and 70th days after sowing). For third treatment (T3) five times application of urea (15th, 30th, 45th, 60th and 75th days). Then for fourth treatment (T4) was six times application of urea (15th, 27th, 39th, 51st , 63rd and 75th days after sowing). The growth parameter were measured as number of tiller, plant height and SPAD. Paddy straw biomass, grains weight and 100 weight grains were measured as rice production parameter. The result showed that there was significant difference in SPAD at second measurement between two varieties which is on MR219. Meanwhile, there were no significant difference in paddy straw biomass, number of tiller, plant height and 100 weight grains. However, significant difference were observed in grain between the treatment on T4.